Nurse effect and soil microorganisms are key to improve the establishment of native plants in a semiarid community. (March 2016) - Molina-Montenegro, Marco A.; Oses, Rómulo; Atala, Cristian; Torres-Díaz, Cristian; Bolados, Gustavo; León-Lobos, Pedro
Abstract: Facilitation by the nurse effect can occur through an amelioration of environmental stress. Plant-microorganism interaction, however, is another key facilitation mechanism of the nurse effect, but is by far the least documented. Here we tested if microclimatic mitigation and soil microorganisms isolated from the root-zone of the nurse shrub Porlieria chilensis can increase the establishment of other native plants in a semiarid community. We conducted field and greenhouse experiments to evaluate the direct and indirect effects of the presence of P. chilensis on the survival and growth of three native plants. In the field experiment, we compared the survival and growth of transplanted individuals beneath nurses and outside of them in pots filled with soil from both microsites (beneath and outside nurses). Finally, in the greenhouse experiment we grew native plants in soil taken from both microsites (below and outside nurses) and with and without soil microorganisms (sterilization process). We found a clear and significant nurse effect of P. chilensis on the tested species through of amelioration of climatic (air temperature, soil moisture, and solar radiation) and edaphic (nitrogen availability) conditions, increasing the performance of these native species. Moreover, performance and establishment were enhanced when soil was kept with microorganisms. Thus, nurse effect mediated by microclimatic amelioration, edaphic improvement and presence of soil microorganisms could be key mechanisms to increase the establishment of native plant species in semiarid communities of central Chile. Highlights: The microorganisms could be a successful mechanism for facilitation process, but few tested in the literature. The facilitation can maintain the structure and biodiversity in plant communities from arid zones of Chile. The nurse effect could be a key mechanism to improve the establishment of endangered flora.